PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE TERHADAP BEHAVIORAL INTENTION YANG DIMEDIASI OLEH USER SATISFACTION PADA NASABAH PENGGUNA APLIKASI BCA SYARIAH MOBILE DI KOTA BANDA ACEH - Vira Astria; Muhammad Basyir (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This research aims to measure the effect of perceived usefulness and perceived ease of use on behavioral intention mediated by user satisfaction on customers that use BCA Syariah Mobile Application in the city of Banda Aceh. Data were collected through a survey of 200 respondents as sample to represents the research population and used a questionnaire as the data collection instrument. The sampling technique used in this research was accidental sampling. Structural Equation Modeling (SEM) was used as analytical method to determine the effect between the variables involved. The results found that perceived usefulness, perceived ease of use, and user satisfaction significantly affects behavioral intention. However, the study did not find a significant effect between perceived usefulness and perceived ease of use on user satisfaction as a result user satisfaction also did not mediate the effects of perceived usefulness and perceived ease of use on behavioral intention.